PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN SARUNG TANGAN DI PT BONA GLOVES - Etty Zuliawati Zed; Adzkia Munifa Rohilawati; Alya Aulia Pane; Filipus Marcell Febrian; Tasya Alisya (Kajian Ekonomi dan Akuntansi Terapan, 2024)
PT BONA MESTY GEMILANG was established in 2002, which has its head office and factory in Cikarang - West Java, PT BONA MESTY GEMILANG is a manufacturer and supplier of Gloves and Personal Protective Equipment in Indonesia. BONA GLOVES produces PU Gloves, Knit Gloves, Rubber / latex gloves, Nitrile Gloves, PVC Gloves, Cotton Fabric Gloves, Nylon Fabric Gloves, Aprons and masks. The purpose of the study was to determine the effect of price and product quality on consumer purchase satisfaction of PT BONA MESTY GEMILANG gloves on Jl. Villa Mutiara Cikarang No.1 Blok G5 19, Ciantra, South Cikarang, Bekasi Regency, West Java 17530. This research method is a quantitative method with data collection techniques based on a questionnaire of 100 people. In determining the sample, the researcher used a nonprobability sampling method and the data collection technique was measured using a Likert Scale from primary and secondary data sources. After the data is collected, the analysis method used by the research is Quality Test, Classical Assumption Test, Multiple Regression Analysis and hypothesis testing. The results showed that partially, the bona gloves variable had a positive and significant effect on purchase satisfaction. The quality variable has a positive and significant effect on purchase satisfaction. The production quality variable has a positive and significant effect on purchase satisfaction